Meningothelial Hamartoma of the Scalp: Clinicopathologic Review of an Unusual Tumor Mimicking a Vascular Neoplasm With Review of Literature. (25th August 2022) - Li, Liping; Merchant, Aziz; Ronen, Shira; Suster, David I.
Abstract: An unusual benign skin lesion is reported in a 19-year-old man with no significant medical history. The lesion had been present since he was an infant and had been slowly enlarging over the past 15 years. The lesion caused pain and discomfort, and the patient underwent an excisional biopsy. Histologic examination showed a subcutaneous lesion with ill-defined borders and peripheral areas of infiltration between adnexal structures. The lesion was composed of small round to ovoid cells embedded in a collagenous stroma with prominent cystic pseudovascular appearing channels causing a pseudopapillary or lymphangitic appearance that mimicked a vascular neoplasm. Immunohistochemistry performed showed positive staining for EMA, progesterone receptor, D2-40, and vimentin within the lesional cells. The tumor cells were negative for cytokeratin AE1/AE3, CD34, CD31, HHV-8, STAT6, SMA, Desmin, S-100, Melan A, and HMB45. A next-generation sequencing study using a hybrid capture-based panel examining 50 commonly mutated genes in human neoplasia was performed and showed no molecular alterations suggesting a nonneoplastic nature. Based on the clinical presentation, histologic features, and results of ancillary studies, the case was diagnosed as a hamartoma of the scalp with meningothelial-like elements. Reported cases of this lesion have behaved in a benign manner; however, as the histologic differential includes low-grade malignant vascular neoplasms such as angiosarcoma, it is important to recognize the salient features of this lesion.